Stabilization of an earthen material with Tung oil: compaction, strength and hydrophobic enhancement. (5th July 2021) - Lin, H.; Liu, F.Y.; Lourenço, S.D.N.; Schwantes, G.; Trumpf, S.; Holohan, D.; Beckett, C.T.S.
Highlights: Tung oil has a time-dependent hardening behaviour. Fresh Tung oil increases the density of compacted soils. Hardened Tung oil bonds particles and enhances the unconfined compressive strength. Tung oil enhances their hydrophobicity with high and persistent contact angles. Abstract: Earthen construction generates interest due to its environmental and economic advantages such as low embodied energy, thermal comfort and low construction cost. Two challenges, namely durability and strength, hinder its application. Tung oil, a sustainable vegetable oil traditionally applied in waterproofing wooden construction, could improve the water resistance and strength of earthen materials. This study aims to detail the multiple roles and mechanisms of Tung oil as a stabilizer. Completely decomposed granite, a natural mineral soil, was selected to assess the influence of Tung oil and its time-hardening behavior on the compaction behaviour, unconfined compressive strength and hydrophobicity. Results revealed that: (1) fresh Tung oil could simultaneously increase the density of compacted soils and decrease the water required for compaction. (2) Tung oil hardened during drying, bonding soil particles and enhancing the unconfined compressive strength of the compacted soils. (3) Hydrophobicity of the stabilized soils were also enhanced, with high and persistent contact angles, which could further contribute to its durability and minimize water-induced damage.